Molecular Characterization of Mycobacterium avium subsp. paratuberculosis (MAP) Water Buffalo in Chitwan, Nepal - Singh, S; Dhakal, I.P.; Singh, U.M.; Devkota, B.N. (Nepalese Veterinary Journal, 2023)
Available within the full article